1412 Cervical spine immobilisation in ambulatory patients. Issue 12 (22nd November 2022) - Phillips, Hannah; Savadia, Krishna; Johnson, Graham
Abstract : Aims, Objectives and Background: Approximately 2500 people suffer a traumatic cervical spinal fracture per year in the UK, of which 10–14% have an associated spinal cord injury. Emergency department practice was changed after Sundstrom et al (2014) found existing evidence for cervical spine collars to be weak. From April 2015 a new guideline was implemented in the Royal Derby Hospital removing the routine use of cervical collars for certain groups. This allowed patients who self-presented to the ED who met the Canadian C-spine criteria for radiographic imaging to remain free from immobilisation devices and undergo standing plain films or self-position for CT imaging. Method and Design: A retrospective case note review was carried out from April 2009 to September 2021. Patients with a confirmed diagnosis of cervical spine fracture were identified and those who did not arrive by ambulance were selected for analysis. Their case notes were reviewed for fracture site, time since injury, neurological symptoms and clinical management. Results and Conclusion: Cervical spine fracture was diagnosed in 30 patients each year on average over the study period. Fifteen per cent were not conveyed by ambulance. Over 70% of patients presented more than 4 hours after their injury. The most common site of injury was C6/7 (50%) followed by C2 (30%). Those patients who self-presented to the emergency department and were subsequently diagnosed with a cervical spine fracture suffered no adverse outcomes. Self-presentation to the emergency